Predicting entrepreneurial intention: A comparison of the theory of reasoned action and the theory of planned behavior - Mohd Ariff, Arifatul Husna; Bidin, Zainol; Sharif, Zakiyah; Ahmad, Adura (ASEAN Universities Consortium of Enterpreneurship Education (AUCEE), 2010)
Purpose - The purpose of this study is to compare the applicability of Theory), of Reasoned Action(TRA) and Theory of Planned Behavior (TPB) in predicting entrepreneurial intention atnong undergraduate students.Desigdmethodology - Data were collected from 121 undergraduate accounting students in Universiti Malaya and Universiti Utara Malaysia. Multiple regression analysis was employed to examine and compare the two competing models in terms of overall fit and explanator), power. Findings - Results showed that both theories are fit in predicting entrepreneurial intention. All variables (attitude, subjective norm and perceived behavioral control) had signrficantly influence the entrepreneurial intention. In TRA, attitude variable is stronger than subjective norm; while in TPB, perceived behavior control variable is stronger than attitude and subjective norm. Based on adjusted R2, TPB model has higher value than TRA model. It shows that TPB model is better than TRA in predicting students' intention towards entrepreneurship of which the perceived behavior control element shall be emphasized. Research limitations/implications - Since the sample consisted ofthe undergraduate accounting students, findings could not be generalized to other undergraduate students. Therefore, a more comprehensive study should be conducted to extend the samples to cover other programs in universities in Malaysia. Practical implications - The policy makers and higher institution should focus on the factors that can influence students' entrepreneurial intention in encouraging them to become entrepreneur after their graduation. Originality/value - This is the first study that compares TRA and TPB applicability in predicting entrepreneurial intention in entrepreneurship context.